2021
DOI: 10.3390/medicina57090957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeinated and Decaffeinated Coffee Consumption on Metabolic Syndrome Parameters: A Systematic Review and Meta-Analysis of Data from Randomised Controlled Trials

Abstract: Coffee is rich in phenolic acids, such as caffeic acid and chlorogenic acid (CGA). Polyphenol-rich diets were shown to reduce the risk of metabolic syndrome (MeTS). Background and Objectives: This systematic review and meta-analysis discusses the effects of coffee consumption and its dose-response on MeTS parameters. Materials and Methods: PubMed and Scopus® were searched for relevant articles published between 2015 and 2020. This review focused on randomised controlled trials (RCTs) investigating the effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
(108 reference statements)
0
14
1
Order By: Relevance
“…We found consistent positive genetic correlations with BMI and obesity in both 23andMe and the UKB. This is in contrast to meta-analyses of randomized control trials and epidemiological studies that found unclear effects by any coffee or decaffeinated coffee intake on waist circumference and BMI-defined obesity, and a modest inverse relationship between coffee intake and BMI 120,121 . Results for these studies are highly heterogeneous, likely due to interindividual variability in the inclusion of sugary coffee additives, cultivation, roasting, and brewing conditions affecting its chemical makeup 9,122 , and other habits surrounding coffee intake (e.g., concurrent food intake or appetite suppression by nicotine if smoking concurrently 123 ).…”
Section: Discussioncontrasting
confidence: 77%
“…We found consistent positive genetic correlations with BMI and obesity in both 23andMe and the UKB. This is in contrast to meta-analyses of randomized control trials and epidemiological studies that found unclear effects by any coffee or decaffeinated coffee intake on waist circumference and BMI-defined obesity, and a modest inverse relationship between coffee intake and BMI 120,121 . Results for these studies are highly heterogeneous, likely due to interindividual variability in the inclusion of sugary coffee additives, cultivation, roasting, and brewing conditions affecting its chemical makeup 9,122 , and other habits surrounding coffee intake (e.g., concurrent food intake or appetite suppression by nicotine if smoking concurrently 123 ).…”
Section: Discussioncontrasting
confidence: 77%
“…Further evidence suggests that it improves endothelial function, aids in loss of fat mass and is associated with favorable plasma biomarkers of metabolic and inflammatory pathways [ 14 , 15 , 16 ]. A recent metanalysis of randomized controlled trials by Ramli et al investigated the effects of coffee consumption on anthropometric measurements, glycemic indices, lipid profiles, and blood pressure and found all of these parameters were improved by green coffee extract supplementation [ 17 ]. It is of great interest to continue to investigate the relationship between coffee consumption and the development of MetS, especially given that there is little prospective epidemiological evidence on the association between coffee consumption and MetS incidence [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants found in coff ee, such as chlorogenic acids (daily dose ranging from 787 mg or 407 mg) have been shown to bring benefi t for cardiovascular health, demonstrated as increased cholesteryl esters, followed by a reduction in oxysterols and free fatty acids levels after daily consumption of a coff ee beverage (400 ml a day) of chlorogenic acids after 8 weeks among apparently healthy adults [44]. Similarly, intake of green coff ee either as extract (from 180 to 376 mg) in a capsule or as a decaff einated coff ee drink (510.6 mg) rich in chlorogenic acid improved the metabolic syndrome symptoms observed as reduced waist circumference, triglyceride levels HDL cholesterol levels, systolic and diastolic blood pressure; and fasting blood glucose levels [45]. Interestingly, the intake of coff ee with added cow's milk has benefi cial eff ects on post-exercise muscle recovery and glycogen levels, after cycling sessions in male athletes.…”
Section: 22mentioning
confidence: 94%